A Comparison in Physical Fitness Attributes, Physical Activity Behaviors, Nutritional Habits, and Nutritional Knowledge Between Elite Male and Female Youth Basketball Players - Sánchez-Díaz, Silvia; Yanci, Javier; Raya-González, Javier; Scanlan, Aaron T.; Castillo, Daniel (Frontiers in Psychology, 2021)
Background: Limited evidence exists comprehensively assessing physical fitness attributes, physical activity behaviors, nutritional habits, and nutritional knowledge according to sex in basketball players during early adolescence. Insight of this nature could be used to optimize the training process and lifestyles in young basketball players. Objective: To compare physical fitness attributes, physical activity levels, nutritional habits, and nutritional knowledge between elite male and female basketball players under 14 years of age (U-14). Methods: Twenty-three U-14 basketball players (male, n = 13 and female, n = 10) from the same elite basketball academy (Spanish Asociación de Clubes de Baloncesto [ACB] League) participated in this study. Physical fitness attributes were assessed using a basketball-specific test battery (countermovement jump, drop jump, linear sprint, Lane Agility Drill, 505 change-of-direction, and repeated-change-of-direction tests), while physical activity levels (Physical Activity Questionnaire for Adolescents, PAQ-A), nutritional habits (Turconi questionnaire), and nutritional knowledge (Turconi questionnaire) were assessed using questionnaires. Results: Male players exhibited better physical fitness in all tests (p <0.001 to 0.036, effect size = -0.44 to -0.76, intermediate to strong) compared to female players. Male players also performed more physical activity in their leisure time (p = 0.036) than females. No significant differences in nutritional habits and nutritional knowledge were evident between sexes (p >0.05). Of note, a high proportion of players declared never or only sometimes eating fruit (males: 23%; females: 40%) and vegetables (males: 46%; females: 70%). In addition, relatively poor nutritional knowledge was evident in all players with the group correctly answering <50% of nutritional questions overall (4.57  1.88 out of 11 points, 42%) and according to sex (males: 4.07  2.10, 37%; females: 5.20  1.40, 47%). Conclusion: These findings emphasize the necessity to perform individualized prescription of training stimuli across sexes to optimize the physical preparedness and development of youth basketball players. Additionally, strategies such as nutrition-focused education interventions may be necessary in this population given the low consumption of fruits and vegetables, as well as the poor nutritional knowledge observed in players.